(untitled) (Conference Zone, 2022)
The article addresses the property rights of authors, its management issues on a collective basis, procedure for establishing copyright management organizations and their reputation. Also, national legislation norms in the field of management of property rights and the issues of relationship between copyright management organizations and authors are discussed.